Contribution to the knowledge of cotylean flatworms (Turbellaria, Polycladida) from Iranian coasts: Introducing a new species, with remarks on new records - Maghsoudlou, Abdolvahab; Rahimian, Hassan (Zootaxa, 2014)
Very little information is available regarding marine free-living flatworms not only from Iran, but throughout the countries surrounding the Persian Gulf and the Gulf of Oman. The present study first introduces a new euryleptid species, and then reports four pseudocerotid polyclads which inhabit Iranian shallow rocky shores of the Persian Gulf and the Gulf of Oman. Maritigrella makranica sp. nov. is characterized dorsally by a medial cream or white reticulated appearance containing pale orange spots in a honeycomb pattern, a distinct orange submarginal band around the entire body margin and between the marginal tentacles, black spots scattered around mid-dorsal surface, becoming more sparse on raised median region and towards body margin, surrounded by a dark-grey halo around the body midline and orange-black halo towards margin. Three of the four pseudocerotids species belonging to the genera Pseudobiceros Faubel, 1984; Pseudoceros Lang, 1884; and Thysanozoon Grube, 1840, are new records for the studied areas, while the other has been reported in the Persian Gulf previously. Comments on Iranian species are provided and associations of flatworms with ascidians and sponges were observed.